Effects of unilateral and bilateral contrast training on the lower limb sports ability of college basketball players - Duan, Tianyu; He, Zongwei; Dai, Jing; Xie, Lin; Shi, Yuer; Chen, Lunxin; Song, Junyi; Li, Guoxing; Zhang, Wenfeng (Frontiers in Physiology, 2024)
Objective: The purpose of this study was to compare the impact of unilateral (U) and bilateral (B) contrast training on lower limb explosiveness, agility, and balance in college basketball athletes.Methods: Twenty male college basketball players were randomly assigned to either a unilateral group (U, n = 10) or a bilateral group (B, n = 10). Both groups underwent an 8week strength training program, with sessions held twice a week. The unilateral group performed six Bulgarian split squats and ten reverse lunge jump squats, while the bilateral group performed six barbell rear squats and ten double-leg vertical jumps. To comprehensively assess the training effects, the study utilized one-repetition maximum (1RM), countermovement jump (CMJ), 20m sprint, and single-leg hop tests to evaluate explosive power; the 505 and t-test to assess change-of-direction ability; and the Y-balance test (YBT) to evaluate dynamic balance. Paired sample t-tests were used to evaluate within-group changes, and a 2 (pre- and post-) × 2 (experimental and control groups) repeated measures analysis of variance (ANOVA) was used to assess between-group differences.Results: Within-group comparisons indicated that both unilateral and bilateral contrast training significantly improved all performance metrics. Between-group comparisons revealed that bilateral training was superior to unilateral training in improvements in 1RM and CMJ (p > 0.05) (growth rate of 1RM: B: 8.4%, U: 5.15%; growth rate of CMJ: B: 15.63%, U: 6.74%). Unilateral training showed greater improvements in the 20m sprint, dominant leg single-leg hop, YBT left, and YBT right (p > 0.05) (growth rate of 20m sprint: B: 5.43%, U: 10.41%; growth rate of advantage foot touch high: B: 4.56%, U: 9.35%; growth rate of YBT left: B: 3.77%, U: 8.53%; growth rate of YBT right: B: 4.72%, U: 13.8%). Unilateral training also significantly outperformed bilateral training in non-dominant leg single-leg hop, t-test, 505 left, and 505 right improvements (p < 0.05).Conclusion: Unilateral contrast training may offer advantages for enhancing change-of-direction ability and explosive power in the non-dominant leg, and it may also provide benefits for improving short-distance sprinting ability, explosive power in the dominant leg, and dynamic balance. In contrast, bilateral contrast training appears to be more effective for enhancing bilateral explosive power and may be more advantageous for increasing maximal strength.